1991
DOI: 10.1103/physrevlett.66.1725
|View full text |Cite
|
Sign up to set email alerts
|

Role of regular steps on the formation of missing-row reconstructions: Oxygen chemisorption on Ni(771)

Abstract: Scanning tunneling microscopy and LEED reveal that on regularly stepped Ni(771) the oxygen-driven missing-row reconstruction of the (110) terraces proceeds in a very transparent manner: Substrate atoms can move to adjacent terraces without crossing steps, where they line up with remaining atom rows to form linear O-Ni chains. On the resulting double-width terraces perfect missing-row structures all over the surface are formed in contrast to flat Ni(l 10); to surmount the double-step barrier, elevated temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…On the contrary, for more open stepped surfaces, showing e.g. (100) or (110) oriented terraces, oxygeninduced faceting occurs [205,258,[283][284][285]. The effect was attributed to the small difference in the surface-free energy between the LMI and the vicinal HMI surfaces compared to the relatively large chemisorption energy of oxygen (> 4 eV), which binds mainly at steps.…”
Section: Oxygen Adsorption At Cu: Adsorbate-induced Reconstruction Anmentioning
confidence: 77%
See 1 more Smart Citation
“…On the contrary, for more open stepped surfaces, showing e.g. (100) or (110) oriented terraces, oxygeninduced faceting occurs [205,258,[283][284][285]. The effect was attributed to the small difference in the surface-free energy between the LMI and the vicinal HMI surfaces compared to the relatively large chemisorption energy of oxygen (> 4 eV), which binds mainly at steps.…”
Section: Oxygen Adsorption At Cu: Adsorbate-induced Reconstruction Anmentioning
confidence: 77%
“…An active role of defects in oxygen adsorption was suggested early [204] but it has been assessed systematically only recently, as indicated by the increasing number of publications on defected systems which has appeared in the last few years. For stepped Ni surfaces, e.g., it was shown that: (a) an O-induced missing row reconstruction occurs on Ni(771) [205]; (b) the reconstruction dynamics of O/Ni(977) is influenced by the oxygen dissolution history of the crystal [206] and (c) the heat of adsorption for oxygen at Ni(211) is considerably higher than on any LMI Ni surface, due to the higher reactivity of under-coordinated atoms [108]. For the less investigated Rh and Ru stepped surfaces the attention concentrated mainly on the chemical activity of step atoms [207,208]; for O 2 /Rh(711) [207] it was demonstrated that (111)-like steps are active sites although they are not always the most stable ones for adsorption.…”
Section: Oxygen Adsorption At Noble and Transition Metal Surfaces: Thmentioning
confidence: 99%
“…The reconstruction process itself was found to proceed via an added row mechanism with steps being a decisive parameter. In the following we present results on a regularly stepped surface, namely Ni(771), to further enlighten the role of steps on the dynamics of MRreconstructions [70,71]. 1 x 2) and Au(551) (1 x 2), which both exhibit terrace widths of an integer number of reconstuction periods.…”
Section: Oxygen Driven Mr-reconstruction Of Ni(771)mentioning
confidence: 98%
“…In Sects. 2 and 3 we discuss our recent results on the reconstruction behaviour of vicinal surfaces of Au(110) [68,69] and Ni(110) [70,71], which give insight into both, the stability of reconstructing vicinals, as well as the influence steps on the dynamics of the reconstruction process. In Sect.…”
mentioning
confidence: 98%
“…On the fee (110) transition metal surfaces two different types of missing-row (MR) reconstructions occur [1]: (i) (1x2) MR structures with every other close-packed row missing (clean Au [2] and Pt [3], induced by small doses of alkalis on Ni [4], Cu [5], Pd [6], and Ag [7]), and (ii) (2x1) MR structures formed upon oxygen adsorption on Ni [8,9], Cu [10,11], and Ag [12] with every other row perpendicular to the close-packed rows missing; oxygen occupies positions close to the long bridge sites [13].…”
mentioning
confidence: 99%